Revealing Academic Stress in Medical Students of Cenderawasih University, Jayapura, Papua Province, Indonesia - Setyarini, Kaida Irma; Makaba, Sarce; Hasmi, Hasmi; Bouway, Dolfinus Yufu; Tingginehe, Rosmin Mariati; Anggai, Martapina Maria (Formosa Journal of Science and Technology, 2024)
The prevalence of stress experienced by Indonesian students is 36.7–71.6%. Academic stress also occurs in students in Papua. However, the causative factors have not been revealed. The aim of this study was to reveal the academic stress of medical students of Cenderawasih University and its related factors. The research used is cross-sectional, sampling technique uses purposive sampling, with a total sample of 188. The research was carried out in December 2023 at the Faculty of Medicine, Cenderawasih University, Jayapura. The result showed a significant and risky relationship with student academic stress are academic factors  (p-value 0.018) RP=2,704, and health conditions (p-value 0.021)  RP=5,143. All of these factors must be managed well by Medical education team management.